Z-Scanning Analysis of Non-Linear Optical Properties of Biodiesel Prepared Via Transesterification Reaction - Ab Razak, Siti Noraiza; Mohamad Aizat Abu Bakar; Nurul Nadia Adnan; Muhammad Sufi Roslan; Mundzir Abdullah; Ganesan Krishnan; Nik Noor Haryatul Eleena Nik Mahmud (Emerging Advances in Integrated Technology, 2026)
This paper explores the nonlinear optical properties (NLO) of biodiesel (BD) produced from waste cooking oil (WCO), a sustainable and environmentally friendly alternative to conventional diesel fuel, using the Z-scan method. The study investigates the optical, chemical, and physical characteristics of BD derived from WCO through transesterification. Both the physical and chemical properties, as well as the NLO, were characterized. The physical and chemical properties and nonlinear optical properties were characterized. The density of BD is 0.85 gcm-3 and kinematic viscosity is 5.76 mm2s-1. The Fourier Transform Infrared (FTIR) spectrum results show methyl ester is presented in BD converted from WCO. The experimental results, obtained using the Z-scan method, revealed that the nonlinear optical properties n2, ? and ?3 are 1.76×10-14 cm2/W, 7.80×10-4 cm/W and 1.046×10-5, respectively. These findings suggest that BD exhibits potential applications in optical switching, laser technology, signal processing, optical limiting, and optoelectronic devices.